Effects of Two Different Doses of Ursodeoxycholic Acid on Indirect Hyperbilirubinemia in Neonates with Glucose-6-phosphate Dehydrogenase Deficiency Treated with Phototherapy: A Randomized Controlled Trial - Roya Farhadi MD; Elham Keyhanian MD; Mohammad Naderisorki MD; Aliasghar Nadi Ghara MSc (SAGE Publishing, 2023)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is one of the causes of severe hyperbilirubinemia, prolonged jaundice, and bilirubin-induced encephalopathy in neonates. In a randomized controlled trial, we evaluated the effect of oral ursodeoxycholic acid (UDCA) on indirect hyperbilirubinemia in G6PD-deficient neonates requiring phototherapy. Intervention group I (N = 45; received phototherapy and 10 mg/kg/day UDCA), Intervention group II (N = 40; received phototherapy and 20 mg/kg/day UDCA), and a control group (N = 49; received phototherapy and placebo). Levels of total serum bilirubin (TSB) in all 3 groups decreased significantly over time ( P  = .001) but the level of TSB at different hours after admission and the duration of phototherapy did not differ significantly between the 3 groups. After discharge, the 2 intervention groups had a significantly lower rate of readmission than the control group ( P  = .001). No significant difference was observed between the 10 and 20 mg/kg/day groups. Further evaluation is recommended, especially in terms of the pharmacokinetics of UDCA in neonates. Trial registration number: IRCT20091201002801N4, prospectively registered on 2019-06-1